Early gestation heat stress influences fetal biomarkers indicative of maternal cortisol transfer in pigs - MaryKate H. Byrd; L. Kirsten Senn; Alex Pasternak; Kara R. Stewart; Jay S. Johnson (Scientific Reports)
Abstract In utero heat stress (IUHS) alters hypothalamic-pituitary-adrenal (HPA) axis development in pigs; however, the mechanisms mediating this effect remain unclear. This study aimed to evaluate cortisol transfer dynamics from the heat-stressed (HS) dam to the IUHS conceptus during early gestation. We hypothesized that gestational HS would modify maternal cortisol secretion and increase conceptus cortisol exposure. Twenty-three gilts were exposed to thermoneutral (TN; n = 11) or HS (n = 12) conditions from gestation d 6 to 33. Maternal vaginal temperature, respiration rate, skin temperatures, and salivary cortisol concentrations were monitored. On d 33, dams were harvested to assess fetal and reproductive tract morphology and collect fetal and placental samples for glucocorticoid and 11β-HSD2 analyses. Heat-stressed gilts exhibited increased (P ≤ 0.01) vaginal temperature, respiration rate, and skin temperatures, but salivary cortisol was similar (P = 0.13). Total and viable fetuses per corpus luteum were reduced (P ≤ 0.05) in HS dams. Fetal tissue cortisone: cortisol tended to be reduced (P = 0.06) and was reduced in IUHS fetus amniotic fluid (P = 0.03). Amniotic fluid cortisone tended to decrease (P = 0.07), while cortisol tended to increase (P = 0.08) in IUHS fetuses. These data suggest IUHS increases fetal glucocorticoid exposure.